Surgical treatment post-intubation tracheal stenosis after severe COVID-19 infection – fundamental aspects of nursing care: a case report - Terech-Skóra, Sylwia; Kwiecień-Jaguś, Katarzyna; Terlecka, Martyna; Kruk, Agnieszka; Piotrkowska, Renata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2023)
Tracheal stenosis, regardless of its aetiology, can seriously affect the ability to breathe, communicate freely, or function daily, increasing morbidity and mortality. Treatment options for tracheal stenosis are extensive and include pharmacotherapy, endoscopic procedures, and surgical treatment, which effectively solves this problem in 95% of cases. Nursing management in the care of a patient undergoing resection and reconstruction of the trachea is rarely discussed in the literature. The prepared article is the first publication of this type in which the specific aspects of postoperative nursing care for a patient after segmental tracheal resection are presented, based on the example of a case report of a 64-year-old woman with post-intubation tracheal stenosis as a result of treatment of COVID-19 infection.